2007
DOI: 10.3390/12051045
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Quercetin on Mushroom Tyrosinase and B16-F10 Melanoma Cells

Abstract: Abstract:In searching for tyrosinase inhibitors from plants using L-3,4-dihydroxyphenylalanine (L-DOPA) as a substrate, quercetin was found to be partially oxidized to the corresponding o-quinone under catalysis by mushroom tyrosinase (EC 1.14.18.1). Simultaneously, L-DOPA was also oxidized to dopaquinone and both o-quinones were further oxidized, respectively. The remaining quercetin partially formed adducts with dopaquinone through a Michael type addition. In general, flavonols form adducts with dopaquinone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 35 publications
3
26
0
Order By: Relevance
“…The presence of quercitrin and rutin, derivatives of quercetin, might be related to the capability of this extract to inhibit tyrosinase and scavenge the DPPH activities. Kubo et al [19] reported the melanin biosynthesis inhibitory activity of quercetin. Rutin was reported to have antioxidant properties [20].…”
Section: Resultsmentioning
confidence: 98%
“…The presence of quercitrin and rutin, derivatives of quercetin, might be related to the capability of this extract to inhibit tyrosinase and scavenge the DPPH activities. Kubo et al [19] reported the melanin biosynthesis inhibitory activity of quercetin. Rutin was reported to have antioxidant properties [20].…”
Section: Resultsmentioning
confidence: 98%
“…Enzymatic action catalyzed by tyrosinase utilizes quercetin as a substrate, which can form reactive o-quinone compounds (82). The activation of quercetin into quinone compounds has been observed in various cell lines, including melanoma cells (10, 11). Subsequently, after the formation of reactive species and metabolized quercetin, the compounds can bind to and deplete GSH, the main bioreductive antioxidant agent to prevent cellular damage (83).…”
Section: Bioreduction Potential and Associated Signaling Cascadesmentioning
confidence: 99%
“…Melanocytes and melanoma cells, in particular, have a unique feature in that they specifically express the oxidative enzyme tyrosinase, which can oxidize quercetin into reactive adducts (10, 11). In this review, we propose that quercetin can be used as a basis for the development of a strategy for melanoma therapeutics.…”
Section: Introductionmentioning
confidence: 99%
“…It is responsible for the formation of mammalian melanin pigments as well as enzymatic browning of fruits and vegetables. Thus, tyrosinase has received great attention, since it is known as a key enzyme in melanin biosynthesis, which plays a crucial protective role against skin photocarcinogenesis (Kubo, Nitoda, & Nihei, 2007;Xue et al, 2011). However, overproduction and accumulation of melanin in the skin can result in pigmentation disorders.…”
Section: Introductionmentioning
confidence: 99%